Establishing safe, effective ablation in the diseased human ventricle: an analysis of generator impedance and electrogram attenuation. (19th May 2022) - Bates, A; Paisey, JR; Yue, A; Banks, P; Roberts, PR; Ullah, W
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Biosense Webster Inc Background: Predictors of effective and safe lesion delivery in the human left ventricle have not been established. Generator impedance (GI) drop and electrogram (EGM) attenuation are indices which can be used as surrogates for ablation lesion parameters. Tissue pops are a complication of myocardial overheating preceded by a rise in GI and can have adverse consequences. Purpose: To establish the relationships between Ablation Index (AI), Force Time Integral (FTI) and contact force with GI and EGM attenuation. To establish factors early in ablation that are predictive of a GI rise. Methods: Patients undergoing ventricular tachycardia ablation were recruited. All ablations were performed with contact force sensing surround flow catheters. Electrograms were collected pre and post ablation, with GI, AI, FTI measured during. Ablations were divided into low (LVM, < 0.50mV), intermediate (IVM, 0.51 – 1.50mV) and normal voltage (NVM, > 1.50mV) based upon pre-ablation bipolar EGM amplitude. Ablations with a 5% rise in GI from maximal drop were noted and predictors of this explored. Results: In 15 patients, 402 ablations were analysed. Filtered percentage GI drop correlated with AI and FTI, (p < 0.0005, Spearman's ρ = 0.522 and 0.524) and reached a plateau at 763AI and 713gs, a filtered GI drop of 7.5% (Figure 1). Shallower curves occurred progressively from NVM to IVM to LVM, (p < 0.0005), (Figure 2) The bipolar EGM significantly attenuated with ablation, (median attenuation 0.14mV, [29.3%], p <0.0005), but percentage attenuation did not correlate with AI or FTI. Parameters associated with a GI rise during ablation were greater mean CF to maximum GI drop, (p = 0.002), greater initial percentage GI drop at 5 seconds, (p < 0.0005), power of 50W (p = 0.005), and perpendicular orientation, (p = 0.006). Percentage GI drop at 5 seconds was the best predictor of ablations with a GI rise, (AUCROC 0.773; 95% CI 0.708 – 0.838; optimal cut-off 2.44%). Mean contact force to maximum GI drop was a poor predictor of a GI rise (AUCROC 0.647; 95% CI 0.577 – 0.718, optimal cut-off 14.7g). Conclusion: During left ventricular ablation, AI of 763 and FTI of 713gs should be targeted, with a lower impedance drop observed for more scarred myocardium. A GI drop of <2.5% at 5 seconds and contact force < 15g should be used to optimise ablation safety.